2020
DOI: 10.1111/sum.12577
|View full text |Cite
|
Sign up to set email alerts
|

Effect of conservation agriculture on soil organic and inorganic carbon sequestration and lability: A study from a rice–wheat cropping system on a calcareous soil of the eastern Indo‐Gangetic Plains

Abstract: Increasing soil carbon (C) in arable soils is an important strategy to achieve sustainable yields and mitigate climate change. We investigated changes in soil organic and inorganic carbon (SOC and SIC) under conservation agriculture (CA) in a calcareous soil of the eastern Indo‐Gangetic Plains of India. The treatments were as follows: conventional‐till rice and wheat (CT‐CT), CT rice and zero‐till wheat (CT‐ZT), ZT direct seeded rice (DSR) and CT wheat (ZT‐CT), ZTDSR and ZT wheat without crop residue retention… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
28
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(31 citation statements)
references
References 15 publications
3
28
0
Order By: Relevance
“…Globally, Zomer et al [63] reported that arable lands have the potential to sequester about 0.90 to 1.85 Pg C year −1 , which corresponds to 26-53% of the target of the "4p1000 Initiative: Soils for Food Security and Climate". In India, Dey et al [49] reported that adopting CA-based management practices for six years sequestered about 2 Mg C ha −1 in the upper 0-15 cm soil layer. However, the influences of CA-based management practices on SOC levels have shown varying results in different soils, climates, and cropping systems [47,48,[113][114][115][116].…”
Section: Conservation Agriculture Contribution To Socmentioning
confidence: 99%
See 1 more Smart Citation
“…Globally, Zomer et al [63] reported that arable lands have the potential to sequester about 0.90 to 1.85 Pg C year −1 , which corresponds to 26-53% of the target of the "4p1000 Initiative: Soils for Food Security and Climate". In India, Dey et al [49] reported that adopting CA-based management practices for six years sequestered about 2 Mg C ha −1 in the upper 0-15 cm soil layer. However, the influences of CA-based management practices on SOC levels have shown varying results in different soils, climates, and cropping systems [47,48,[113][114][115][116].…”
Section: Conservation Agriculture Contribution To Socmentioning
confidence: 99%
“…However, the consequences of climate change could be mitigated by Conservation agriculture and its components have been associated with many bene fits, including carbon (C) storing in the soil [22,26,48,52,[57][58][59][60][61][62][63], improved soil qualit [26,56,[64][65][66][67][68][69][70], decreasing runoff and soil erosion [2,[71][72][73][74], increasing water productivit [6,51,68,75,76], energy use efficiency [77,78], and, in some cases, higher yield and profita bility [6,[79][80][81]. Accordingly, CA has emerged as a promising approach and viable optio Conservation agriculture and its components have been associated with many benefits, including carbon (C) storing in the soil [22,26,49,53,[58][59][60][61][62][63]…”
Section: Introductionmentioning
confidence: 99%
“…To prevent bias due to variation in soil ρ b (Mg m −3 ) and take into full account the effect of soil mass on SOC stock 68 . Thus, we have calculated total SOC stocks on an equivalent soil mass (ESM) using formula 69 where, M soil is the soil mass and ESM is the equivalent soil mass …”
Section: Methodsmentioning
confidence: 99%
“…According to an analysis of soil organic carbon data from 1980 to 2015 in the semiarid regions of China, soil carbon storage could increase by 453%–757%, if optimal cultivated land type, mulching material type and planting method were selected (Xiao et al., 2020). Conservation agriculture practices, such as zero tillage and residue retention, could potentially improve carbon sequestration in surficial soil (Dey et al., 2020). A 36‐year long‐term study found that no tillage resulted in 1.5 t C ha −1 of soil organic matter in comparison with conventional tillage (Govindasamy et al., 2021).…”
Section: Soil Carbon Sequestrationmentioning
confidence: 99%
“…For deeper soil, different studies have rendered contrasting results on the impact of conservation agriculture on soil carbon storage (Dey et al., 2020; Govindasamy et al., 2021), which may be dependent on the soil mineral types as calcareous soil can also store inorganic carbon. The soil carbon dynamic is also influenced by the reaction occurring on the surface of clay minerals, for example poorly crystalline Fe and Al increased the C saturation, thus causing more carbon desorption and microbial decomposition (Khandakar et al., 2021).…”
Section: Soil Carbon Sequestrationmentioning
confidence: 99%